2008
DOI: 10.3390/md20080005
|View full text |Cite
|
Sign up to set email alerts
|

Yessotoxins, a Group of Marine Polyether Toxins: an Overview

Abstract: Yessotoxin (YTX) is a marine polyether toxin that was first isolated in 1986 from the scallop Patinopecten yessoensis. Subsequently, it was reported that YTX is produced by the dinoflagellates Protoceratium reticulatum, Lingulodinium polyedrum and Gonyaulax spinifera. YTXs have been associated with diarrhetic shellfish poisoning (DSP) because they are often simultaneously extracted with DSP toxins, and give positive results when tested in the conventional mouse bioassay for DSP toxins. However, recent evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 102 publications
(119 reference statements)
1
57
0
2
Order By: Relevance
“…There are reports on damages in cardiac muscle (Aune et al, 2002), liver and pancreas (Terao et al, 1990), and neuronal tissue (Franchini et al, 2004) by intraperitoneal YTX supply in mice. Consequently, YTX should be considered a potential risk for human health with a lethal dose (LD50) between 80 and 750 mg/kg (Paz et al, 2008). Besides the possible toxic effects of YTX, it has been suggested that YTX may act as a defense against grazers as feeding rates by copepods were significantly reduced in the presence of YTX (Makino et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports on damages in cardiac muscle (Aune et al, 2002), liver and pancreas (Terao et al, 1990), and neuronal tissue (Franchini et al, 2004) by intraperitoneal YTX supply in mice. Consequently, YTX should be considered a potential risk for human health with a lethal dose (LD50) between 80 and 750 mg/kg (Paz et al, 2008). Besides the possible toxic effects of YTX, it has been suggested that YTX may act as a defense against grazers as feeding rates by copepods were significantly reduced in the presence of YTX (Makino et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the possible toxic effects of YTX, it has been suggested that YTX may act as a defense against grazers as feeding rates by copepods were significantly reduced in the presence of YTX (Makino et al, 2008). Yessotoxin has been found in bivalves and phytoplankton samples in many places around the world (Paz et al, 2008), with records from Norway (Ramstad et al, 2001;Miles et al, 2004) and the Russian White Sea (Vershinin et al, 2006), indicating a subarctic and arctic occurrence. A future expansion in distribution and an increase in bloom formation potential of toxin producing species such as P. reticulatum will have a significant impact, as marine products are assumed to be of increasing economic importance for Greenland and other arctic and subarctic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Other non-toxic strains of L. polyedrum from Norway, Spain and California (USA) have also been reported (Armstrong & Kudela, 2006). In contrast, toxic strains have been reported from Italy, the United Kingdom, Ireland, Galicia and Andalucía (Spain) (Paz, Riobó, Fernández, Fraga, & Franco, 2004;Paz et al, 2008) and California (USA) (Armstrong & Kudela, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The L. polyedrum extracts were examined for the possible presence of yessotoxins (YTXs) and some analogs and derivatives (Table 2), as this dinoflagellate is a known producer of YTXs (Paz et al, 2008). YTXs were extracted from 50 mL of late-exponential phase L. polyedrum culture, centrifuged for 10 min each at 2 500 × g and then at 20 000 × g, as above.…”
Section: Toxin Extraction and Analysismentioning
confidence: 99%
“…There are more than 36 compounds in this group of toxins [61]. Like other groups of marine toxins, yessotoxins have phytoplanktonic origin (Protoceratium reticulatum, Lingulodinium polyedrum, Gonyaulax spinifera) [62][63][64] and a worldwide distribution [61,65].…”
Section: Yessotoxinsmentioning
confidence: 99%